Reply to: When adopting Global Lung Function Initiative reference values, can we also adapt them to a local context as needed?. Issue 3 (16th September 2021) - Stanojevic, Sanja; Cooper, Brendan; Filipow, Nicole; Kirkby, Jane; Ruppel, Gregg; Steenbruggen, Irene; Thompson, Bruce; Hall, Graham
We thank S. Verbanck and co-workers for their insightful response to the recent official European Respiratory Society technical standards for Global Lung Function Initiative (GLI) reference lung volumes [1]. The data presented highlight the real-world impact of using published equations and how equipment or protocol offsets can impact clinical interpretation. We generally agree with S. Verbanck and co-workers that more precise approaches are ideal, and that is the ultimate goal of the GLI Network. Global Lung Function Initiative reference equations help to standardise interpretation of pulmonary function tests; however, there is a need to balance precision and generalisability with the uncertainty of interpretation https://bit.ly/3iheRFv